El reino de las moscas - Mimbela Menendez, Lucia (2022)
The present project consists of the layout, illustration, graphic design and literary creation of the horror story compilation book, titled “El reino de las moscas”, of digital selfpublication with the addition of a small marketing campaign on Instagram. The purpose of this project is that, at the end of it all, there will be a complete book layout ready to publish, with a good reception from the key demographic and that it resonates with lovers of the horror genre, especially with young women who, hopefully, will feel identified with the family issues the characters of these stories persevere throughout the duration of the book.